Language Assessment Literacy of a Vietnamese EFL University Lecturer: A Qualitative Case Study - Tran Thi Tuyet Mai (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Assessment literacy plays an important role in language teaching, helping teachers make the right decisions to support learners' learning. This qualitative case study clarified the language assessment literacy of a university EFL teacher at a public university in Vietnam. The data were collected through a semi-structured interview and analysed according to Giraldo’s framework, which consists of three dimensions: knowledge, skills, and principles. The findings show that the participant has a clear conceptual understanding of the different assessment purposes, closely align with expected learning outcomes and program objectives. However, she encounters numerous challenges at the macro and micro levels and must negotiate her way to meet the standards while helping her students reach their final objectives. The study illustrates how language assessment literacy is perceived and translated into practice in a higher education context in Vietnam and proposes suggestions regarding professional development and future research.